2008
DOI: 10.1111/j.1745-9125.2008.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

A Methodological Addition to the Cross‐national Empirical Literature on Social Structure and Homicide: A First Test of the Poverty‐homicide Thesis*

Abstract: Dozens of cross‐national studies of homicide have been published in the last three decades. Although nearly all these studies test for an association between inequality and homicide, no studies test for a poverty—homicide association. This absence is disconcerting given that poverty is one of the most consistent predictors of area homicide rates in the abundant empirical literature on social structure and homicide in the United States. Using a sample that coincides closely with similar recent studies, applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 25 publications
6
181
0
7
Order By: Relevance
“…Literature on the feminization of poverty demonstrates that women may be much more greatly impacted by poverty than men (for a review of this literature see Bianchi, 1999), and using overall poverty measures would not capture these gender differences. Recent research has made important strides in empirical assessment of the poverty-homicide relationship (Pridemore, 2008), but sex-specific measures of poverty are not yet available for a large number of countries.…”
Section: Discussionmentioning
confidence: 99%
“…Literature on the feminization of poverty demonstrates that women may be much more greatly impacted by poverty than men (for a review of this literature see Bianchi, 1999), and using overall poverty measures would not capture these gender differences. Recent research has made important strides in empirical assessment of the poverty-homicide relationship (Pridemore, 2008), but sex-specific measures of poverty are not yet available for a large number of countries.…”
Section: Discussionmentioning
confidence: 99%
“…Sampson & Lauritsen, 1994) as well as cross-nationally (Messner & Rosenfeld, 1999;Nivette, 2011;Pridemore, 2008Pridemore, , 2011Pridemore & Trent, 2010) has shown that poverty is a robust predictor of area crime. These findings place poverty as an essential component for the current models.…”
Section: Control Variablesmentioning
confidence: 95%
“…Spatial analyses are useful when a social phenomenon is thought to grow nonrandomly and in a nonlinear fashion, and there is evidence to believe this is the case for homicide (Tita & Radil, 2010). For instance, we know by a wealth of American and international literature that homicide, and more generally violence, is not distributed evenly throughout the population and tends to cluster in disadvantaged, usually urban, space (Land, McCall, & Cohen, 1990;McCall, Land, & Parker, 2010;Pratt & Cullen, 2005;Pridemore, 2008;Pridemore & Trent, 2010).…”
Section: Spatial Patterns Of Legitimacy and Homicidementioning
confidence: 98%
See 1 more Smart Citation
“…Urbanization: Rural-urban migration and high unemployment rates and attendant poverty with income inequality [25]. Use of psychoactive substances: This is quite common in the two cities.…”
Section: Similaritiesmentioning
confidence: 99%